MODELS OF TEACHING MATERIALS FOR APPRECIATION OF FICTION PROSE LOCAL LOADED - Grinitha, Virry; Nugroho, Agung; ., jamaludin; ., Cekman (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2023)
This study aims to develop a teaching material model for prose fiction appreciation with local content that suits the needs of students and lecturers. The research method is Research and development (R&D) with the Dick and Carey teaching material development model which includes needs analysis, learning analysis, student and context analysis, formulating performance objectives, developing instruments, developing learning strategies, developing and selecting learning materials, formative evaluation and revision . The research subjects were study program students. Indonesian Language and Literature UNPARI Lubuklinggau. Data collection techniques by conducting interviews and questionnaires. Data analysis techniques using a Likert scale, validity test and practicality test. Research Results The results of design validation are included in the valid category with a total percentage of 77%. Language validation with a valid category of 64% percentage. Validation of valid category material with a total percentage of 78%. The total number of validation results is 72.6% which is categorized as valid, so that the teaching materials have been used effectively. The results of one to one trials in the practical category with a total percentage of 80%, small group trials of 78.7%. Based on the results of research on the development of a model of teaching materials for appreciation of prose fiction, it is valid and practical.